Ciulirnerunak yuuyaqunak = Do not live without an elder : the subsistence way of life in southwest Alaska - Fienup-Riordan, Ann (University of Alaska Press, 2016)
"In October of 2010, six men who were serving on the board of the Calista Elders Council (CEC) gathered in Anchorage with CEC staff to spend three days speaking about the subsistence way of life. The men shared stories of their early years growing up on the land and harvesting through the seasons, and the dangers they encountered there. The gathering was striking for its regional breadth, as elders came from the Bering Sea coast as well as the Yukon and Kuskokwim rivers. And while their accounts had some commonalities, they also served to demonstrate the wide range of different approaches to subsistence in different regions. This book gathers the men's stories for the current generation and those to come. Taken together, they become more than simply oral histories--rather, they testify to the importance of transmitting memories and culture and of preserving knowledge of vanishing ways of life"--